Communicating User Experience: Applying Local Strategies Research to Digital Media Design - Milburn, Trudy (2015)
Communicating User Experience illustrates how the use of Local Strategies Research (LSR) methodologies enables designers to understand the cultural implications for user actions and practices in a...
Keywords: dept.aa